COVID-19 Exposure During Neurology Practice: Results of American Academy of Neurology Survey. Issue 6 (4th November 2021) - Qureshi, Adnan I.; Rheaume, Carol; Huang, Wei; Lobanova, Iryna; Govindarajan, Raghav; French, Brandi R.; Siddiq, Farhan; Gomez, Camilo R.; Sahota, Pradeep K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: To determine the exposure risk for coronavirus 2019 (COVID-19) during neurology practice. Neurological manifestations of COVID-19 are increasingly being recognized mandating high level of participation by neurologists. Methods: An American Academy of Neurology survey inquiring about various aspects of COVID-19 exposure was sent to a random sample of 800 active American Academy of Neurology members who work in the United States. Use of second tier protection (1 or more including sterile gloves, surgical gown, protective goggles/face shield but not N95 mask) or maximum protection (N95 mask in addition to second tier protection) during clinical encounter with suspected/confirmed COVID-19 patients was inquired. Results: Of the 81 respondents, 38% indicated exposure to COVID-19 at work, 1% at home, and none outside of work/home. Of the 28 respondents who did experience at least 1 symptom of COVID-19, tiredness (32%) or diarrhea (8%) were reported. One respondent tested positive out of 12 (17%) of respondents who were tested for COVID-19 within the last 2 weeks. One respondent received health care at an emergency department/urgent care or was hospitalized related to COVID-19. When seeing patients, maximum protection personal protective equipment was used either always or most of the times by 16% of respondents in outpatient setting and 56% of respondents in inpatient settings, respectively. Conclusions: The data could enhance our knowledge of the factors that contribute to COVID-19 exposure during neurology practice in United States, and inform education and advocacy efforts to neurology providers, trainees, and patients in this unprecedented pandemic.